2013
DOI: 10.1073/pnas.1310589110
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone is a cellular senescence target in pituitary and nonpituitary cells

Abstract: Premature proliferative arrest in benign or early-stage tumors induced by oncoproteins, chromosomal instability, or DNA damage is associated with p53/p21 activation, culminating in either senescence or apoptosis, depending on cell context. Growth hormone (GH) elicits direct peripheral metabolic actions as well as growth effects mediated by insulin-like growth factor 1 (IGF1). Locally produced peripheral tissue GH, in contrast to circulating pituitary-derived endocrine GH, has been proposed to be both proapopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 86 publications
2
53
0
1
Order By: Relevance
“…High circulating GH levels can be caused by a GH-secreting pituitary tumor, and local colon GH can be induced as a result of DNA damage (51) or inflammation as within the pituitary gland (94). Regardless of the origin, high GH appears to exhibit properties of a component of the field change milieu affecting normal colon cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High circulating GH levels can be caused by a GH-secreting pituitary tumor, and local colon GH can be induced as a result of DNA damage (51) or inflammation as within the pituitary gland (94). Regardless of the origin, high GH appears to exhibit properties of a component of the field change milieu affecting normal colon cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation and real-time PCR, SA-β-galactosidase Activity, cell proliferation assay and motility assay were performed as previously described (51,95). For details, see SI Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already reported that murine pituitary adenomas with altered PTTG and Rb expression trigger cellular senescence (Chesnokova et al 2007(Chesnokova et al , 2008. These authors also correlated the high levels of growth hormone (GH) with the senescence-associated markers in adenomas, and suggested that cellular senescence is activated in a lineage-specific fashion ( Chesnokova et al 2008Chesnokova et al , 2011Chesnokova et al , 2013. However, to date, no attempt has been made to analyze the emergence of cellular senescence with pituitary tumor progression in the absence of genetic manipulation or specific senescence-inducing stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…pituitary senescence being a cytological stress response (Marcotte et al 2004). In this way, senescence might be a more appropriate mechanism for pituitary tumor suppression, taking into account that the pituitary gland is critical for the homeostatic function, but which exhibits a regenerative capacity (Chesnokova et al 2013).…”
Section: Discussionmentioning
confidence: 99%